(untitled) (Journal of Asian Development Studies, 2024)
Autism Spectrum Disorder (ASD) presents unique challenges in behaviour management, requiring tailored approaches. This paper explores the impediments academic psychologists face in administering Behavior Management Techniques (BMTs) for children and adults diagnosed with ASD. Qualitative research was employed to discover the views of academic psychologists. The investigator selected the participants through a purposive sampling technique and performed semi-structured interviews to accumulate the views. Academic psychologists within the Punjab province, Pakistan, were taken as the population of the study. The group of five academic psychologists was selected purposefully to discover the phenomenon. Academic psychologists were recruited from the Govt. Special Education Centers, along with the experience of diverse clinical settings, hospital practices and clinical sessions with children and adults diagnosed with ASD. Twelve open-ended questions were designed to inquire from the respondents and to facilitate a deeper dialogue about the phenomenon of the study. Reflexive thematic analysis was employed over the views of academic psychologists. The analysis process involved coding the data to perceive the patterns of the data. Patterns were prepared into broader themes and then sub-themes to increase the complete understanding of the statistics. Key impediments were identified, including communication challenges, sensory sensitivities, individualized needs, and lack of parental involvement. Understanding these impediments is crucial for developing effective interventions and improving outcomes for children and adults diagnosed with ASD.